NGOs, civil society, and the public sphere - Lang, Sabine, 1959- (Cambridge : Cambridge University Press, 2013)
'Nongovernmental organizations act on behalf of citizens in politics and society. Yet many question their legitimacy and ask who they speak for. This book investigates how NGOs can become stronger advocates for citizens and better representatives of their interests. Sabine Lang analyzes the choices that NGOs face in their work for policy change between working in institutional settings and practicing public advocacy that incorporates constituents' voices. Whereas most books on NGOs focus on policy effectiveness, using approaches that treat accountability largely as a matter of internal performance measurements, Lang instead argues that it is ultimately several public accountabilities that inform NGO legitimacy. The case studies in this book use empirical research from the European Union, the United States, and Germany to point to governments' role in redefining the conditions for NGOs' public advocacy'--
Includes bibliographical references and index.
Keywords: Non-governmental organizations; Civil society